Prenatal Smoke Exposure Predicts Hyperactive/Impulsive but Not Inattentive ADHD Symptoms in Adolescent and Young Adult Girls - Gard, Arianna M. (Infant Child Dev, 2015)
We examined the longitudinal associations between prenatal tobacco smoke exposure (PSE) and attention-deficit hyperactivity disorder (ADHD) symptom domains in adolescence and young adulthood. A sample of girls with ADHD combined presentation (N=93), ADHD predominantly inattentive presentation (N=47), and matched comparisons (N= 88) was assessed prospectively. Symptoms of hyperactivity/impulsivity (HI), inattention (IA), and oppositionality (oppositional defiant disorder) were measured via multiple informants 5 (M age =14 years; retention rate =92%) and 10 years (M age =20 years; retention rate =95%) following childhood ascertainment. PSE was captured via maternal self-report. We used linear regressions to examine the prediction from PSE to both HI and IA in adolescence and early adulthood after stringent control of relevant confounding variables. PSE significantly predicted HI during adolescence and young adulthood across multiple informants but did not predict IA at either wave. Symptoms of HI may have partial etiological independence from IA symptoms.